Pyrrolidine dithiocarbamate ameliorates rotenone-induced Parkinson's disease in rats - Noha F. Abdelkader; Nadia M. Arafa; Amina S. Attia; Afaf A. Ain-Shoka; Dalaal M. Abdallah (Faculty of Pharmacy, Cairo University, 2017)
Pyrrolidine dithiocarbamate (PDTC), a low-molecular-weight thiol antioxidant, possesses neuroprotection; however, its possible modulatory effect in Parkinson's disease (PD) has not been tested. Male Wistar rats were injected with rotenone to induce PD-like symptoms. Histopathological findings showed that striatal neurons were degenerated following rotenone administration, an effect that was accompanied by behavioral deficits. Furthermore, rotenone decreased striatal dopamine (DA) and glutamate and prominently increased serotonin, GABA, glutathione (GSH), thiobarbituric acid reactive substances (TBARS), and myeloperoxidase (MPO) levels. Daily treatment with PDTC protected against rotenone induced changes at the microscopic level, decreased the extent of motor dysfunctions, and markedly increased DA and suppressed glutamate levels. It also reduced TBARS, GSH, and MPO. Whereas, rotenone neither affected striatal caspase-3 activity nor tumor necrosis factor-α level, PDTC treatment reduced the later. The current study reveals the effectiveness of PDTC against rotenone-induced PD via enhancement of DA, as well as antioxidant and anti-inflammatory properties.